Penerapan Metode Game Development Life Cycle pada Game Edukasi Pengenalan Sejarah Suku Kluet - Muhammad Fadhil; Fera Damayanti; Sarudin, Sarudin (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
Understanding history is often hindered by various constraints, including limited engaging learning media and insufficient attention to the culture of the Kluet tribe. To overcome these obstacles, efforts such as developing engaging learning media, promoting cultural understanding programs, and creating special educational games to introduce the Kluet tribe are necessary. Educational games for history introduction serve as an interesting alternative to introduce the Kluet tribe interactively. The use of technology in education, especially educational games, has attracted attention as an effective means in the learning process. This research will explain the use of the Game Development Life Cycle (GDLC) method in developing an educational game for introducing the history of the Kluet tribe. Based on the questionnaire results provided to users, 85% of respondents stated that this educational game on the history of the Kluet tribe is engaging and interactive.